2021
DOI: 10.1021/acsomega.1c05145
|View full text |Cite
|
Sign up to set email alerts
|

Transformer-Based Generative Model Accelerating the Development of Novel BRAF Inhibitors

Abstract: The de novo drug design based on SMILES format is a typical sequence-processing problem. Previous methods based on recurrent neural network (RNN) exhibit limitation in capturing long-range dependency, resulting in a high invalid percentage in generated molecules. Recent studies have shown the potential of Transformer architecture to increase the capacity of handling sequence data. In this work, the encoder module in the Transformer is used to build a generative model. First, we train a Transformer-encoder-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…9 a–c, and e the Tr model is much less stable under RL optimization compared to the RNN and more readily undergoes mode collapse i.e., it starts generating invalid or repeated (non-unique) molecules, as shown in Additional file 1 : Figures S18-19. In fact, very few implementations of transformers exist within a RL setting (e.g., [ 104 , 105 ]) likely due to this instability during training and computational expense, sometimes being distilled to an RNN for RL [ 10 ]. Therefore we additionally implemented a modified transformer architecture designed to stabilize model optimization during RL [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…9 a–c, and e the Tr model is much less stable under RL optimization compared to the RNN and more readily undergoes mode collapse i.e., it starts generating invalid or repeated (non-unique) molecules, as shown in Additional file 1 : Figures S18-19. In fact, very few implementations of transformers exist within a RL setting (e.g., [ 104 , 105 ]) likely due to this instability during training and computational expense, sometimes being distilled to an RNN for RL [ 10 ]. Therefore we additionally implemented a modified transformer architecture designed to stabilize model optimization during RL [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Algorithms such as gated recurrent unit (GRU), long short-term memory (LSTM), and Transformer are widely used to extract sequence features and directly used to build predictive models, among which models with Transformer as the basic building block achieve state-of-the-art performance in most NLP-based classification and regression tasks. 10,19 Examples include the Bert model based on the Transformer encoder and the GPT model based on the Transformer decoder. 20,21 The Bert model has been well used in NLP tasks, such as a question answering system, text classification and entity extraction.…”
Section: Methodsmentioning
confidence: 99%
“…9 Among them, reinforcement learning (RL) is used as an optimization algorithm and docking software is used as a scoring function to find a small molecule with the highest affinity for binding to the target in the chemical space. 10,11 However, the coordinated optimization of PD and PK properties in molecule generation tasks remains a great challenge for most existing models, 12 especially when they focus on the pursuit of affinity for the lead compound. Therefore, the subsequent lead-optimization work is very necessary.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the 1-layer GRU performs comparable to the 4-layer GRU and can be successfully used for small molecule library design. 22 Therefore, we use the above model to accelerate the development of antibacterial drugs, and the trained stack-augmented GRU is saved as a pretrained model to be weighted by a task-specific transfer learning model.…”
Section: Methodsmentioning
confidence: 99%